Is pretreatment cystometry important in predicting response to mirabegron in women with overactive bladder symptoms?. Issue 3 (March 2016) - Basu, Maya; Balachandran, Aswini; Duckett, Jonathan
Abstract Introduction and hypothesis The aim of this study was to evaluate for any association between pretreatment cystometry results and outcome of treatment with mirabegron in women with overactive bladder (OAB) symptoms. Methods This was a prospective observational study of women with OAB symptoms that proved refractory to conservative management. All women underwent filling and voiding subtraction cystometry prior to further treatment. Women were treated with mirabegron 50 mg once daily, and outcomes were evaluated after 6 weeks' treatment. The primary outcome measure was change in symptoms as indicated by response to the Patient Global Impression of Improvement (PGI-I) scale. The presence of detrusor overactivity (DO), the highest detrusor pressure recorded during the filling phase, the presence of urodynamic stress incontinence (USI), cystometric capacity, voided volume, maximum flow rate and detrusor pressure at maximum flow were all compared between responders and nonresponders. Results The study population consisted of 169 women; response rate to mirabegron was 69.8 %. There was no association between the presence of DO or maximum detrusor pressure during filling and USI, cystometric capacity, maximum flow rate and detrusor pressure at maximum flow and treatment response. In a subgroup with OAB symptoms refractory to previous treatment with antimuscarinics, there was an association between the presence of DO and a positive treatment response (p  = 0.02). Conclusions Overall, there is no association between urodynamic findings and response to treatment with mirabegron. This may reflect the fact that mirabegron's mode of action mechanisms are not measurable using cystometry. In women with refractory symptoms, however, the presence of DO is associated with a positive response to treatment.